Assessment of development results - the Republic of the Philippines evaluation of UNDP contribution The Republic of the Philippines. - United Nations Development Programme. Evaluation Office (New York, NY United Nations Development Programme, Evaluation Office, 2009)
This ADR has examined contribution made by the United Nations Development Programme (UNDP) to development results and its strategic positioning in the Philippines during the latest two programming cycles: 2001-2009.
"March 2009."--Title page.
Includes bibliographical references (pages 75-77).
Keywords: Economics -- Business -- Economic development -- Philippines